2016
DOI: 10.1038/ncomms11254
|View full text |Cite
|
Sign up to set email alerts
|

A small number of abnormal brain connections predicts adult autism spectrum disorder

Abstract: Although autism spectrum disorder (ASD) is a serious lifelong condition, its underlying neural mechanism remains unclear. Recently, neuroimaging-based classifiers for ASD and typically developed (TD) individuals were developed to identify the abnormality of functional connections (FCs). Due to over-fitting and interferential effects of varying measurement conditions and demographic distributions, no classifiers have been strictly validated for independent cohorts. Here we overcome these difficulties by develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
328
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 271 publications
(349 citation statements)
references
References 67 publications
18
328
1
2
Order By: Relevance
“…One is that FCNef can be directly applied to rs-fc-based abnormal connectivity, or a biomarker, in networks [32–34]. For clinical purposes, connectivity-based neurofeedback techniques including FCNef need to be combined with the biomarkers that characterize psychiatric disorders based on rs-fcMRI.…”
Section: New Neurofeedback Techniques Resulting From the Integrationmentioning
confidence: 99%
See 2 more Smart Citations
“…One is that FCNef can be directly applied to rs-fc-based abnormal connectivity, or a biomarker, in networks [32–34]. For clinical purposes, connectivity-based neurofeedback techniques including FCNef need to be combined with the biomarkers that characterize psychiatric disorders based on rs-fcMRI.…”
Section: New Neurofeedback Techniques Resulting From the Integrationmentioning
confidence: 99%
“…Regrettably, early studies of biomarkers suffered from overfitting of machine learning algorithms and did not exhibit generalization capability for completely independent validation cohorts [70–74]. However, the recent development of sophisticated machine learning algorithms has overcome these technical problems and led to the production of rs-fcMRI-based biomarkers, which are capable of classifying patients from controls with high accuracy and generalization to completely independent cohorts [32–34,75]. Development of these robust rs-fcMRI-based biomarkers have allowed FCNef, which is also rs-fcMRI-based, to directly modify them.…”
Section: New Neurofeedback Techniques Resulting From the Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of classification methods, the accuracy of the SVM is comparable with that seen in other machine learning-based disease biomarkers that have used independent validation cohorts ( Takagi et al , 2017; Yahata et al , 2016) (albeit less than that seen with classifiers for phasic BOLD responses to acute painful stimulation in healthy individuals ( Wager et al , 2013)). Here, we also applied a deep learning approach using deep convolutional neural networks, the utility of which has not previously been tested in chronic pain.…”
Section: Discussionmentioning
confidence: 72%
“…One way to tackle this is to use machine learning and deep learning methods, and a number of studies have shown how this can be used to successfully build biomarkers (i.e. classifiers) in a range of psychiatric disease ( Takagi et al , 2017; Watanabe et al , 2017; Yahata et al , 2016; Yamada et al , 2017). However, these methods need to be validated on genuinely independent data sets to be convincing, and current evidence of generalisable classifiers for chronic pain is lacking.…”
Section: Introductionmentioning
confidence: 99%